2001
DOI: 10.1097/00001756-200102120-00043
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of stimulus equivalence

Abstract: In order to study brain activation during the formation of equivalence relations, 12 subjects underwent fMRI during matching-to-sample (MTS) tests of (1) previously trained arbitrary relationships between iconic stimuli and the untrained, emergent relations of (2) symmetry, (3) transitivity, and (4) symmetry with transitivity, plus a test of verbal fluency (VF). Brain activation was similar in all MTS tasks and in the VF task. In particular, both types of task activated dorsolateral prefrontal cortex (DLPFC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 18 publications
3
31
0
2
Order By: Relevance
“…The slice selection used by Acuna et al (2002a) did not cover the medial temporal lobe. Other recent studies of transitive inference using verbal premise pairs (Goel and Dolan, 2001) or iconic stimuli (Dickins et al, 2001) also reported significant prefrontal and parietal cortex activation. Of interest, patients with prefrontal cortex damage exhibit deficits in the integration of relations (Waltz et al, 1999), as do patients with schizophrenia (Titone et al, in press).…”
Section: Neural Circuitry Of Transitive Inferencementioning
confidence: 76%
“…The slice selection used by Acuna et al (2002a) did not cover the medial temporal lobe. Other recent studies of transitive inference using verbal premise pairs (Goel and Dolan, 2001) or iconic stimuli (Dickins et al, 2001) also reported significant prefrontal and parietal cortex activation. Of interest, patients with prefrontal cortex damage exhibit deficits in the integration of relations (Waltz et al, 1999), as do patients with schizophrenia (Titone et al, in press).…”
Section: Neural Circuitry Of Transitive Inferencementioning
confidence: 76%
“…The current data are important in that only one published study has undertaken an investigation of the neural correlates of derived relational responding (Dickins et al, 2001, who used fMRI). The current research employed Table 9 Results of Scheffé post hoc tests comparing area dimensions (mV 3 ms), 350 to 550 ms, for the directly trained, equivalent, and nonequivalent trial types for each of the 10 electrode sites, with percentage of individual participants (in parentheses) conforming to the direction of the statistically significant effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies suggest that brain activation is bilateral for tasks that use a semantic criterion (Dickins et al, 2001). Semantic tasks are impaired in patients with lesions in both hemispheres, which suggests that the semantic process for lexical generation depends on the collaboration of both hemispheres (Borovsky, Saygin, Bates, & Dronkers, 2007).…”
mentioning
confidence: 99%